2016
DOI: 10.1007/s11557-016-1197-5
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic and phylogenetic study of the Golovinomyces biocellatus complex (Erysiphales, Ascomycota) using asexual state morphology and rDNA sequence data

Abstract: The Golovinomyces biocellatus complex consists of powdery mildew (Erysiphales) species restricted to hosts of the family Lamiaceae. Previous authors used minor morphological features of the sexual state and host range data to split the complex. The data, however, were not sufficient to define a convincing species concept. Our taxonomic study is based on molecular phylogenetic and asexual state morphology data. For morphological studies, mainly features of the asexual morph (conidiophores, conidia, germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
28
0
2
Order By: Relevance
“…Golovinomyces is characterized by having chasmothecia with mycelioid appendages, several, mostly 2spored asci, an asexual morph with catenescent conidia that lack fibrosin bodies, and mostly nipple-shaped appressoria. Golovinomyces currently encompasses 57 species and 5 varieties [1,[8][9][10][11][12][13]. Erysiphe cichoracearum [14] included nearly all of the species that are now assigned to Golovinomyces.…”
Section: Introductionmentioning
confidence: 99%
“…Golovinomyces is characterized by having chasmothecia with mycelioid appendages, several, mostly 2spored asci, an asexual morph with catenescent conidia that lack fibrosin bodies, and mostly nipple-shaped appressoria. Golovinomyces currently encompasses 57 species and 5 varieties [1,[8][9][10][11][12][13]. Erysiphe cichoracearum [14] included nearly all of the species that are now assigned to Golovinomyces.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report of powdery mildew caused by Golovinomyces monardae on peppermint in Italy. According to taxonomic and phylogenetic studies of the Golovinomyces biocellatus complex (Scholler et al 2016) the same pathogen has been reported on peppermint in Germany, on Mentha spicata in Italy and on other hosts belonging to Lamiaceae and Verbenaceae (Garibaldi et al 2010;Scholler et al 2016 …”
mentioning
confidence: 79%
“…Based on morphology, the causal agent was determined as Golovonomyces spp. (Scholler et al 2016). The internal transcribed spacer region of rDNA of the pathogen was amplified using the primers ITS1/ITS4 and sequenced (GenBank Accession MG205583).…”
mentioning
confidence: 99%
“…Although ITS sequences are commonly and widely used for powdery mildews, they are often not sufficiently reliable for final taxonomic conclusions on the species level [23,24]. However, in this scenario, sequence data are indispensable for the clarification of the G. cynoglossi complex.…”
Section: Discussionmentioning
confidence: 99%